The Individual Therapy Process Questionnaire: Development and Validation of a Revised Measure to Evaluate General Change Mechanisms in Psychotherapy. (6th March 2014) - Mander, Johannes; Schlarb, Angelika; Teufel, Martin; Keller, Ferdinand; Hautzinger, Martin; Zipfel, Stephan; Wittorf, Andreas; Sammet, Isa
<x xml:space="preserve">Abstract</x> There is a dearth of measures specifically designed to assess empirically validated mechanisms of therapeutic change. To fill in this research gap, the aim of the current study was to develop a measure that covers a large variety of empirically validated mechanisms of change with corresponding versions for the patient and therapist. To develop an instrument that is based on several important change process frameworks, we combined two established change mechanisms instruments: the Scale for the Multiperspective Assessment of General Change Mechanisms in Psychotherapy (SACiP) and the Scale of the Therapeutic Alliance—Revised (STA‐R). In our study, 457 psychosomatic inpatients completed the SACiP and the STA‐R and diverse outcome measures in early, middle and late stages of psychotherapy. Data analyses were conducted using factor analyses and multilevel modelling. The psychometric properties of the resulting Individual Therapy Process Questionnaire were generally good to excellent, as demonstrated by (a) exploratory factor analyses on both patient and therapist ratings, (b) CFA on later measuring times, (c) high internal consistencies and (d) significant outcome predictive effects. The parallel forms of the ITPQ deliver opportunities to compare the patient and therapist perspectives for a broader range of facets of change mechanisms than was hitherto possible. Consequently, the measure can be applied in future research to more specifically analyse different change mechanism profiles in session‐to‐session development and outcome prediction. Copyright © 2014 John Wiley & Sons, Ltd. Key Practitioner Message This article describes the development of an instrument that measures general mechanisms of change in psychotherapy from both the patient and therapist perspectives. Post‐session item ratings from both the patient and therapist can be used as feedback to optimize therapeutic processes. We provide a detailed discussion of measures developed to evaluate therapeutic change mechanisms.